(untitled) (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we make use of the generalized Sălăgean differential operator to define a novel class of bi-univalent functions that is associated with the generalized hyperbolic sine function in the open unit disk D. The prime goal of this paper to derive sharp coefficient bounds in open unit disk D, especially the first two coefficient bounds for the functions belong to this class . The investigation also focuses on studying the classical Fekete-Szegö functional problem for functions belong to this class. Furthermore, some known corollaries are highlighted based on the unique choices of the parameters involved in this class.